Dependence on non timber forest products (NTFP) for the sustainable livelihood enhancement of tribals of western Attappady - Ashish Alex (Department of Forest Management and Utilisation, College of Forestry, 2014)
Non-Timber Forest Products (NTFP) play a crucial role in the daily life and welfare of people all over the world. The livelihoods of the people living close to the forest and within the forests are inextricably linked to the forest ecosystem. In Kerala, out of 4000 tribal settlements, 671 settlements are forest settlements, which depended on NTFPs for meeting their various requirements. The present study was conducted in the Western part of Attappady among the three tribal groups namely; Irula, Muduga and Kurumba. The main objective of the study was to document the NTFPs collected and utilized by the tribes for their sustainable livelihood and explore the various marketing mechanisms followed in Western Attappady. A pre-tested questionnaire survey and semi structured interviews were conducted in fifty houses from each community. Secondary data were collected from the cooperative societies, SC/ST Federation and Silent Valley National Park Wildlife Warden’s Office etc. The Irula community who are basically daily wage workers settled on the lower plains of the valley had the highest literacy rate and obtained one per cent of their income from NTFP collection. The Mudugas settled on the midlands had the least literacy rate and derived 9 per cent of their income from NTFP collection. The particular vulnerable tribal group Kurumba settled in the interior areas of the forests obtained 44 per cent of their income from NTFP collection. The tribes of Western Attappady depended on 17 plant species for food, 19 for medicine, 8 for construction and firewood and 6 for religious purpose. The Irulas collected 9 commercial NTFPs, whereas Mudugas and Kurumbas collected 14 and 18 NTFPs respectively. The Irula and Muduga were mostly involved in the collection of honey, whereas Kurumbas involved in the collection of Acacia concinna. The NTFPs have contributed an annual income of Rs. 5755, Rs. 27220 and Rs. 46255 to the Irulas, Mudugas and Kurumbas households respectively.The Irulas got maximum income (Rs. 2880/annum) from honey, whereas Mudugas and Kurumbas got the highest income from Canarium strictum (Rs. 4800/annum) and Solanum torvum (Rs 5880/annum) respectively. Honey was collected only by men and roots were collected by women. In Irula, both the genders made equal contribution to their income from NTFP, whereas in Mudugas the men and women contributed 65 and 35 per cent respectively. The Kurumba women contributed 56 per cent of their income from NTFP collection. The most of the medicinal plants whose roots were the exploitable part were harvested during November to February. The Irulas made 30 trips/ year for NTFP collection, whereas Mudugas and Irulas undertook 78 and 123 trips/year respectively. The three institutions involved in the marketing of NTFPs were Kurumba Cooperative society, Eco shop of EDC and private traders. The Kurumba was marketing most of the NTFPs through the Kurumba society, whereas Irula and Muduga marketed NTFPs through the private shops. The private traders gave better price to the collectors than the society. For Irulas and Mudugas NTFP collection was a subsidiary source of income, whereas for Kurumbas, it was the major source of income. The private traders maintained a constant link with the tribes and ensured the private marketing channels are always active.